Ideology and Insurrection: Bringing the Actor Back In - Grenier, Yvon (CIENCIA ergo-sum, 2017)
This article is the product of a research on ideas, ideologies and political change, with a special focus on El Salvador. It attempts to summarize some of my ideas on ideologies and political change in general -with a special attention to the so-called revolutionary ideologies- hoping that will have relevance to similar issues in other Latin American countries or to global trends. Two broad propositions are presented here:                     1) Ideology is a powerful "causer" of political change. It is neither the mirror of its immediate social and economic environment, nor a purely national product. 2) Revolutionary ideologies play a fundamental role at all stages of so-called "revolutions" but even more so at the stage of emergence of insurrectionary forces, and especially in contemporary developing countries.